Penguatan Kepribadian Remaja Melalui Bimbingan Kelompok di Panti Asuhan Aisyah Putri Payakumbuh - Angelina Anastasha; Sri Hartati (Universitas 45 Surabaya, 2024)
An orphanage is a social institution that helps and guides children's personality development and acquires work skills so that they have a good and dignified future and can be responsible for themselves, their families and society. An effective person is a person who is able to empower himself, develop into a quality person and realize his life goals. People with effective character can be flexible, disciplined, responsible, hardworking, caring, honest, empathetic. The aim of the author's research is to strengthen teenagers' personalities through a group training process. Group training aims to develop individual potential by analyzing the source of problems, overcoming problems and developing personal strength and self-confidence through a discussion atmosphere that uses group dynamics. The problem that the author found in orphanages was that there were foster children who lacked self-confidence, did not want to hang out with their friends and wanted to go home with their parents, and there were even foster children who were bullied. . This type of research uses qualitative rates with a case study method. This research was located at the Aisyyah Putri Payakumbuh Orphanage. Data collection techniques through observation and interviews. Samples were collected using purposive sampling. Data analysis uses data collection techniques, data validity and conclusion drawing. The results of this research show that counselors' strategies for improving teenagers' personalities are implemented in groups by providing services, so that foster children can develop close relationships with their peers and train foster children to be more courageous in expressing their opinions and feelings. The obstacle encountered by counselors when carrying out group counseling is realizing that there are still foster children who are still unable to speak in public, so counselors have difficulty understanding foster children.